2001
DOI: 10.1103/physrevb.65.024511
|View full text |Cite
|
Sign up to set email alerts
|

Smooth vortex precession in superfluid4He

Abstract: We have measured a precessing superfluid vortex line, stretched from a wire to the wall of a cylindrical cell. By contrast to previous experiments with a similar geometry, the motion along the wall is smooth. The key difference is probably that our wire is substantially off center. We verify several numerical predictions about the motion, including an asymmetry in the precession signature, the behavior of pinning events, and the temperature dependence of the precession.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
4
8
0
Order By: Relevance
“…First, from the theoretical point of view it will provide an easier way to describe the role of the particle mass in the vortex dynamics and its effect on vortex excitations. On the other hand, such setting is similar to recent experiments that study the nanowire formation by the coalescence of gold nanofragments on quantum vortices [31] or experiments with vibrating wires inside quantum vortices in superfluid 3 He and 4 He [32,33]. Finally, Fig.…”
Section: Motion Of Particles Trapped By Quantum Vortexsupporting
confidence: 83%
“…First, from the theoretical point of view it will provide an easier way to describe the role of the particle mass in the vortex dynamics and its effect on vortex excitations. On the other hand, such setting is similar to recent experiments that study the nanowire formation by the coalescence of gold nanofragments on quantum vortices [31] or experiments with vibrating wires inside quantum vortices in superfluid 3 He and 4 He [32,33]. Finally, Fig.…”
Section: Motion Of Particles Trapped By Quantum Vortexsupporting
confidence: 83%
“…We do not take these as evidence of a non-quantum vortex trapped along the entire wire; rather, they indicate that a quantized vortex covers only a fraction of the wire and hence has a reduced effect on its vibration frequencies. The clean and reproducible signatures we find in several situations [15,18] confirm this interpretation. As noted above, we can use the frequency splitting of the vibrational modes as an instantaneous measurement of the length of wire covered by the vortex.…”
Section: Methodssupporting
confidence: 83%
“…In the thin half of the cell, the much steeper slope corresponds to energy loss of 47×10 −12 erg/s. Previous experimental [15] and computational [23] work has found that changes in energy loss and precession period are related, with an increase in dissipation corresponding to a longer period. However, that relationship holds for precession within a cell of fixed diameter, not for the change in precession period with cell diameter that we observe here.…”
Section: Dissipationmentioning
confidence: 93%
See 1 more Smart Citation
“…Conveniently, direct comparison between superfluid hydrodynamics calculations and experiment becomes possible. In several cases such simulations accurately describe non-trivial experimental behaviors [5,6].Here we compare vortex pinning in experiment and calculation, finding discrepancies that may indicate a need to modify the computational treatment of surfaces. Our measurements track a single vortex in superfluid helium interacting with a macroscopic bump.…”
mentioning
confidence: 88%